Safety and efficacy of esketamine for postoperative analgesia in pediatric patients with hypospadias - Xu, Yong; Chen, Quan; Li, Ping; Song, Xingrong (Frontiers in Surgery, 2023)
Objective: To explore the safety and efficacy of the combination of continuous intravenous infusion of esketamine with sacral block for postoperative analgesia in pediatric patients undergoing surgery for hypospadias Methods: Pediatric patients (n=77) undergoing surgery for hypospadias at the Guangzhou Women and Children Medical Center between November 1, 2021 and April 30, 2022 were randomized into two groups: a hydromorphone group (H group, initial dose, 0.02 mg/kg; maintenance dose, 0.01 mg/kg/h) or an esketamine group (E group, initial dose, 0.3 mg/kg; maintenance dose 0.15 mg/kg/h). Caudal epidural block involved injection of 0.2% ropivacaine 1 ml/kg through the sacral hiatus. Patients’ age, weight, grade of hypospadias, intraoperative blood loss, operative time and recovery time; FLACC and Ramsay sedation scores when leaving the PACU (0 h) and at postoperative 2, 6, 12, 24, 36 and 48 h; postoperative complications; and urinary tryptophan, 5-hydroxytryptamine, arginine and substance P levels were recorded. Results: There were no significant differences in FLACC scores at postoperative 0, 2, 6, 12, 24, 36, and 48 h in patients who received hydromorphone or patients who received esketamine or between patients who received hydromorphone and patients who received esketamine. Ramsay sedation scores were significantly lower at postoperative 2, 12, and 36 h in patients who received hydromorphone compared to patients who received esketamine. The incidence of hypotension and respiratory depression was significantly higher, and the time to first bowel movement was significantly longer, in patients who received hydromorphone compared to patients who received esketamine. Urinary tryptophan, 5-hydroxytryptamine, arginine, and substance P levels were significantly higher in patients who received hydromorphone compared to patients who received esketamine. Conclusions: The combination of continuous intravenous infusion of esketamine with sacral block provided safe and effective postoperative analgesia for pediatric patients undergoing surgery for hypospadias.